Poetics of visibility in the contemporary Arab American novel - Naous, Mazen (Columbus : The Ohio State University Press, 2020)
""Redefines dominant perceptions of Arab Americans via an aesthetic analysis of Arab American novels, such as Diana Abu-Jaber's Arabian Jazz and Crescent, Rabih Alameddine's Koolaids: The Art of War, Laila Halaby's Once in a Promised Land, and Mohja Kahf's The Girl in the Tangerine Scarf, thereby launching transcultural possibilities by initiating visibility through poetics"--Provided by publisher"--
Introduction: Poetics of Visibility, Visible Poetics -- The Disease as Queer Cure: Rabih Alameddine's Koolaids: The Art of War -- Blue Notes and Accented Rhythms: Diana Abu-Jaber's Arabian Jazz -- Sign after Sign: Mohja Kahf's The Girl in the Tangerine Scarf -- Anagrams of Identity: Laila Halaby's Once in a Promised Land -- Reframing Infidelity: Diana Abu-Jaber's Crescent -- Conclusion: Arab American Polyphonics.
Online resource, title from digital title page (viewed on February 22, 2021).
Includes bibliographical references and index
JSTOR
Keywords: American fiction -- Arab American authors -- History and criticism; American fiction -- 20th century -- History and criticism; American fiction -- 21st century -- History and criticism; Arab Americans in literature; Marginality, Social, in literature; Identity (Psychology) in literature; Roman américain -- 20e siècle -- Histoire et critique; Roman américain -- 21e siècle -- Histoire et critique; Américains d'origine arabe dans la littérature.; Identité (Psychologie) dans la littérature.; LITERARY CRITICISM / General; American fiction; American fiction -- Arab American authors; Arab Americans in literature; Identity (Psychology) in literature; Marginality, Social, in literature; 1900-2099; Criticism, interpretation, etc